Pengalihan Objek Jaminan Fidusia Oleh Debitur Tanpa Persetujuan Kreditur Dalam Perjanjian Kredit Bank - romlan prasodjo (Justicia Journal, 2016)
In the credit agreement, Financial Institutions (both bank and non-bank) always requires a guarantee that must be met to be able to get a loan. The credit agreement with a fiduciary is the measures taken in order to adapt it to the business world and the needs of the community. One of them will be discussed in this thesis that the object of fiduciary transfer of the bank credit agreement. Debtor acts by diverting the object of fiduciary without creditors' approval by reselling to third parties.The approach used is the approach taken by based on laws and regulations (statute approach), which is the approach taken to examine all laws and regulations relevant to the legal issues being addressed, as it also used the conceptual approach (conceptual approach ) approach that is referring to the definitions, concepts and opinions or arguments jurists. And issues to be discussed are legal consequences if the debtor objects fiduciary transferred without the consent of the creditors in the bank credit agreement, as well as legal protection for creditors to object the transfer of fiduciary by the debtor without the consent of the creditor.The legal consequences if the debtor to transfer the object of fiduciary without the consent of the lender based on the right material attached to the fiduciary and the nature of the droit de suite where such rights follow the object in the hands of anyone the object is, the creditor has the right to withdraw security object fiduciary and execution. Execution of fiduciary guarantee the seizure and sale of objects which became the object of fiduciary insurance for injury debtor promise to the creditor. Legal protection for creditors to object the transfer of fiduciary is by registering and insuring fiduciary guarantee object fiduciary. If no registration fiduciary guarantee it will not issue a certificate fiduciary, which means the deed of fiduciary considered to have no binding legal force, while the insured object fiduciary for the purpose of transfer of risk in the event of undesirable events such as the transfer of objects fiduciary by the debtor.